A study of parasites and MHCIIα in Arctic charr(Salvelinus alpinus) - Santos, Cristina Bajo (2011)
Arctic charr (Salvelinus alpinus) is a curious salmonid species due to its geographical situation and possibly sympatric evolution. In Lake Thingvallavatn different morphs with different behavior and feeding patterns cohabit. Though the different morphs differ in many characteristics such as size, color and form, they have similar genetic base. Nevertheless, recently were discovered the presence of immunological differences between dwarf and murta in Thingvallavatn, in the MHCIIα locus specifically. Previous studies indicate MHC heterozygotes have higher survival likelihood than homozygotes. In our study we have processed 264 individuals among three of the different morphs searching for a possible connection between parasite load and different physical (sex, weight, age, location) or genetic (polymorphism in the MHCIIα region) factors. We found some connections or correlations between some of the parasites studied (Diphyllobothrium sp., Dyplostomum sp., Eubothrium salvelini and Nematodes) and some physical variables (weight and age) as we expected but genetic results were unpredicted. This may because our genotyping sample is small. In conclusion, parasite load is directly related with morph and some physical factors and aims to be directly related with MHCIIα polymorphism but we have not enough analyzed data to make our hypothesis consistent.